A política de compra de dívida corporativa do Banco Central Europeu e o seu impacto na emissão de capital próprio - Mauad, Rogério Paulucci (2019)
In response to the economic crisis of 2008 and the debt crises of some eurozone countries, several central banks began expansionary monetary policies, which became a massive injection of resources through the purchase of assets known as Quantitative Easing. The European Central Bank (ECB) took a step forward with its peers and, in addition to buying sovereign bonds through the Public Sector Purchase Program (PSPP), it also created the Corporate Sector Purchase Program (CSPP) in March 2016 to buy corporate bonds from non-financial companies located in the euro zone, with ratings rated higher by rating agencies. The PSPP program led risk-free interest rates to negative levels and the CSPP program reduced corporate yields for both companies with bonds eligible for purchase and those whose bonds are not purchased by the ECB. This thesis is devoted to investigating the effects of the CSPP program on the seasoned equity offerings and to conjecture the moment these programs dedicated to purchase sovereign and corporate assets begin to close and their possible future effects on equity issues in the euro area companies. Using the event study methodology, the results indicate that the cumulative abnormal return (CAR) of the SEOs carried out after the CSPP announcement generated even more negative returns, when compared to those conducted prior to this economic policy, suggesting that, even with low corporate yields, investors are demanding higher equity returns.